Social Entrepreneurship di Masa Web 2.0 [Social Entrepreneurship in the Age of Web 2.0] - Sudirman, Jimmy Sab; Layman, Chrisanty V. (Universitas Pelita Harapan, 2022)
This study aims to examine the positive influence of web 2.0 strategic support, web 2.0 technology use, absorptive capacity, learning CSR against social entrepreneurship, Whereas the sampling technique for this study determined as a non-probability sampling with purposive sampling technique. Samples were taken in the amount of 266 respondents who have been committed as students who are studying and learning about entrepreneurship. The data were collected by distributing electronic questionnaires Likert scale through social media with Google Form. Moreover, this research uses Partial Least Square - Structural Equation Modelling (PLS-SEM) for the statistical analytic method. This study also uses a descriptive type of research with quantitative data. The test results from this study concluded that the specified variables are positive influence on each other.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk menguji pengaruh positif dukungan strategi web 2.0, penggunaan teknologi web 2.0, daya serap, pembelajaran CSR terhadap kewirausahaan sosial. Sedangkan teknik pengambilan sampel untuk penelitian ini adalah non-probability sampling dengan teknik purposive sampling. Sampel yang diambil sebanyak 266 responden yang telah berkomitmen sebagai mahasiswa yang sedang belajar dan belajar tentang kewirausahaan. Pengumpulan data dilakukan dengan menyebarkan angket elektronik skala Likert melalui media sosial dengan Google Form. Selain itu penelitian ini Partial Least Square - Structural Equation Modeling (PLS-SEM) untuk metode statistik analitik. Penelitian ini juga menggunakan jenis penelitian deskriptif dengan data kuantitatif. Hasil uji dari penelitian ini menyimpulkan bahwa variabel yang ditentukan saling berpengaruh positif.